K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

\((2x-1)(3-2x)(1-x)>0 \)

\(\Leftrightarrow\)\(4x^3-12x^2+11x-3>0\)

Bấm máy tính, ta được: \(\left[{}\begin{matrix}\frac{1}{2}< x< 1\\\frac{3}{2}< x\end{matrix}\right.\)

Kết luận ...

10 tháng 10 2018

\(\left(2x+3\right)\left(x-1\right)+\left(2x-3\right)\left(1-x\right)=0\)

\(\left(2x+3\right)\left(x-1\right)-\left(2x-3\right)\left(x-1\right)=0\)

\(\left(x-1\right)\left(2x+3-2x+3\right)=0\)

\(\left(x-1\right)\cdot6=0\)

\(\Rightarrow x-1=0\)

\(\Rightarrow x=1\)

10 tháng 10 2018

(2x+3).(x-1) + (2x-3).(1-x) = 0

(2x+3).(x-1) - (2x+3).(1-x) = 0

(2x+3).[(x-1) - (1-x)] = 0

(2x+3).( x - 1 -1 + x) = 0

(2x+1). ( 2x - 2) = 0

(2x+1).2.(x-1) = 0

=> 2x+1 = 0 => 2x = -1 => x = -1/2

x-1=0 => x = 1

14 tháng 7 2021

(4x-3)(2x-5) +(3-4x)(x-1)=0

(4x-3)(2x-5)-(4x-3)(x-1)=0

(4x-3)(2x-5-x+1)=0

(4x-3)(x-4)=0

4x-3=0 hoặc x-4=0

x=\(\frac{3}{4}\)hoặc x=4